Edukasi Kesehatan tentang Pentingnya Minum Air Putih bagi Remaja di SMP Negeri 1 Kolaka - Ekawati Saputri; Evodius Nasus; Rosani Naim; Grace Tedy Tulak (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Water is an essential component in the body that plays a role in various physiological functions, including concentration and learning performance in adolescents. However, teenagers' awareness to consume enough water is still low. This service activity aims to increase the knowledge and awareness of SMP Negeri 1 Kolaka students about the importance of drinking water through health education. The activity method was carried out by interactive counseling using PowerPoint media displayed through an LCD projector and conducted in the school hall on 19 November 2024, attended by 70 students from classes VII to IX. The material was delivered in an engaging manner and was complemented by discussion sessions. The results of the activity showed an increase in student enthusiasm and participation, as well as an awareness to start bringing drinking water to school and reduce the consumption of sugary drinks. This activity proved effective in fostering students' understanding of the importance of adequate hydration for health. The students expressed a greater willingness to incorporate healthier habits, particularly bringing water to school and making informed choices about hydration. Moreover, they became more aware of the negative impacts of sugary drinks. The activity's success highlights the importance of continued support from schools to create a healthy learning environment and to encourage healthy behaviors that can positively impact students' overall health and academic performance.